Sign languages in bilingual education: a multilingual and multicultural approach - Alcina Madueño, Alfredo (Avances en Supervisión Educativa, 2010)
The bilingual fact when deaf people are concerned has always been a self-evident ability that allows the non-hearing people to interact with their hearing fellows through speaking -at any degree of development-, lip-reading and literacy as helping tools for that purpose. In closest and more private circles, most non-hearing people have used and carry on using sign languages.